Recent adventive soft scale insects (Hemiptera: Coccomorpha: Coccidae) and mealybugs (Hemiptera: Coccomorpha: Pseudococcidae) in India - Joshi, Sunil; Gupta, Ankita; Shashank, P.r.; Pai, Sachin G.; Mohan, M.; Rachana, R.r.; Dubey, Vinod Kumar; Sandeep, Angalakuditi; Deepthy, K.b. (Zootaxa, 2022)
Four species of soft scale insect [Hemiptera: Coccidae: Fistulococcus pokfulamensis Hodgson & Martin, Kilifia deltoides De Lotto, Maacoccus piperis (Green) and Paralecanium machili Takahashi] and two species of mealybug [Hemiptera: Pseudococcidae: Antonina thaiensis Takahashi and Formicococcus simplicior (Green)] are recorded in India for the first time. Each of the six species is comprehensively diagnosed based on Indian material, and compared with earlier descriptions. Keys to the Indian species in their respective genera are provided to facilitate identification. Ecological information on host plants, associated ants and natural enemies is also given.